Expression of vesicular glutamate transporters in sensory and autonomic neurons innervating the mouse urinary bladder - Brumovsky, Pablo Rodolfo (2013)
Purpose: Vesicular glutamate transporters (VGLUTs), essential for loading glutamate into synaptic vesicles, are present in various neuronal systems. However, the expression of VGLUTs in neurons innervating the urinary bladder has not yet been analyzed. Here, we study the presence of VGLUTs type-1, -2 and -3 (VGLUT1, VGLUT2 and VGLUT3, respectively) in mouse urinary bladder neurons. Materials and Methods: Expression of VGLUT1, VGLUT2 and calcitonin gene-related peptide (CGRP) was analyzed by immunohistochemistry in retrogradely labeled primary afferent and autonomic neurons of BALB/C mice after injecting Fast Blue in the urinary bladder wall. To study VGLUT3, retrograde tracing of the urinary bladder was performed in transgenic mice where VGLUT3 is identified by detection of enhanced green fluorescent protein (EGFP). Results: Most urinary bladder DRG neurons expressed VGLUT2. A smaller percentage of neurons also expressed VGLUT1 or VGLUT3. Coexpression with CGRP was only observed for VGLUT2. Occasional VGLUT2-immunoreactive (IR) neurons were seen in the major pelvic ganglion (MPG). Abundant VGLUT2-IR nerves were detected in the urinary bladder dome, trigone and also the urethra; VGLUT1-IR nerves were discretely present. Conclusions: We present novel data on the expression of VGLUTs in sensory and autonomic neurons innervating the mouse urinary bladder. The frequent association of VGLUT2 and CGRP in sensory neurons suggests interactions between glutamatergic and peptidergic neurotransmissions, potentially influencing commonly perceived sensations in the urinary bladder, such as discomfort and pain.